The Implementation of Total Physical Response in English Learning for Attention Deficit Hyperactivity Disorder Students - Kadek Nesya Febi Pramesti (Journal of Educational Study, 2021)
English becomes an international language to help people who have different mother tongue to communicate each other. Learning English is very important because it also helps to increase the quality of human resource. Each individual has right to learn English without exception. Students with Attention Deficit Hyperactivity Disorder also can learn English. This study aimed is to describe the process implementation of Total Physical Response method in teaching English and the response from students with Attention Deficit Hyperactivity Disorder. This study uses descriptive qualitative as research design with observation and interview. The participants in this study are five students who have Attention Deficit Hyperactivity Disorder in one of special need schools in Bali.  The result of this study shows that implementing Total Physical Response method, students are easy to remember the new words in English and they also practice the word physically and verbally. Total Physical Response method makes students feeling comfortable and enjoy in teaching and learning process. They are also being motivated and active in the English class.